Characterization and Structural Determination of Cold-Adapted Monodehydroascorbate Reductase, MDHAR, from the Antarctic Hairgrass Deschampsia Antarctica - Ae Kyung Park; Il-Sup Kim; Hackwon Do; Hyun Kim; Woong Choi; Seung-Woo Jo; Seung Chul Shin; Jun Hyuck Lee; Ho-Sung Yoon; Han-Woo Kim (Crystals, 2019)
Ascorbic acid (AsA) is an abundant component of plants and acts as a strong and active antioxidant. In order to maintain the antioxidative capacity of AsA, the rapid regeneration of AsA is regulated by dehydroascorbate reductase (DHAR) and monodehydroascorbate reductase (MDHAR). To understand how MDHAR functions under extreme temperature conditions, this study characterized its biochemical properties and determined the crystal structure of MDHAR from the Antarctic hairgrass Deschampsia antarctica (DaMDHAR) at 2.2 Å resolution. This allowed for a structural comparison with the mesophilic MDHAR from Oryza sativa L. japonica (OsMDHAR). In the functional analysis, yeast cells expressing DaMDHAR were tolerant to freezing and thawing cycles. It is possible that the expression of DaMDHAR in yeast enhanced the tolerance for ROS-induced abiotic stress.